AID PROHIBITION AS A TOOL OF THE U.S. FOREIGN POLICY: DE JURE AND DE FACTO - V. I. Bartenev (MGIMO University Press, 2019)
The United States is indisputable global leader in utilizing tools of economic statecraft to secure national interests both through rewarding foreign countries for policies conforming the Washington interests and through punishing them for a deviant behavior. Foreign assistance is one of such mechanisms of global influence. This paper examines the issue of aid prohibition. The first section contains a catalog and an original typology of effective universal (not country-specific) restrictions on foreign aid provision based on the type of the recipient government’s actions or inactions through its domestic policy or international behavior that trigger harming the U.S. economic interests. The paper demonstrates that such a typology is equally applicable to the U.S. bilateral and multilateral aid and invites to differentiate between the restrictions within one category depending on whether they are imposed in response to the recipient’s actions against the United States or to its international policy as a whole. The second section assess the extent to which the U.S. government is consistent in imposing the aid restrictions. The conclusion is drawn that the U.S. has established a parallel (to the international law) legal regime of aid prohibitions that helps them control the developing countries’ behavior. Most of the active restrictions and prohibitions were imposed during the Cold War but not as byproducts of the bipolarity, which is another illustration of continuity in the U.S. global policies in the 20th and 21st centuries. The imposition of these restrictions reflects not only a diversification of external threats to the U.S. vital interests, but also the logic of the U.S. domestic political process and the legislators’ wish to restrain the executive branch. The President, however, is entitled by law to waive most of the norms out of political or strategic considerations. This helps the U.S. government impose restrictions selectively but does not eliminate a hypothetical risk of aid suspension that can refrain a recipient government from certain domestic or external actions. Nonetheless, the impact of the U.S. aid prohibition as a tool of coercion has been declining because of strengthening of non-Western donors – especially, China, Arab countries, Turkey and Russian Federation.